Sleep quality and attention of senior high school students - Christine Kurniawan; Meiyanti Meiyanti (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Background: A successful learning process can be influenced by an individual’s attention level that can affect his/her concentration level and memory capacity. Some psychological and neurological aspects contribute to the attention level. If an individual experiences attention disorder, he/she can be difficult to learn and work efficiently. One of factors that may affect the individual’s attention is sleeping quality. A sufficient sleeping quality plays an important role in an individual’s development and daily activities.Objective: This study aims to analyse relationships between the sleeping quality and the attention of students to improve their learning performances.Methods: This study was an observational analysis study with a cross-sectional design that involved 87 senior high school students. The inclusion criteria of this study were male/female students between 14 to 19 years old who were willing to be respondents by signing informed consent form. Its exclusion criteria were male/female students who were experiencing brain-related injuries and who were on medical treatment causing drowsiness such as influenza drugs, cough syrups and sleeping pills. This study was conducted for four months. The data were collected by interviews and questionnaires including identity data, educational level, Pittsburgh Sleep Quality Index valuation and digit span tests. The samples were collected with a consecutive non-random sampling method. Its data analysis was conducted by applying SPSS V.21 through Chi-Square statistical test with a significance level of 0.05.Results: Of the 87 respondents, 50.6% were females and 35.6% were 15 years old. The majority of them were at class X (10th grade). Also, 52.9% of them had low sleeping quality and 74% of them suffered bad attention. Based on the Chi-Square test, the relationship between the sleeping quality and the attention level was not significant with p value of 0.938. Conclusion: There was no a significant relationship between the sleeping quality and the attention levels on the senior high school students.